2014
DOI: 10.1159/000365388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise on Cognitive Performance in Older Adults with Mild Cognitive Impairment or Dementia: A Systematic Review

Abstract: Numerous studies have shown that physical exercise has positive effects on cognition in healthy adults. Less is known about the effectiveness of exercise interventions in older individuals already suffering from mild cognitive impairment (MCI) or dementia. The aim of this study was to systematically review the evidence from randomized controlled trials (RCTs) of the effects of physical exercise on cognition in older subjects with MCI or dementia. PubMed, Cochrane and DARE databases were systematically searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
184
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(207 citation statements)
references
References 46 publications
5
184
0
2
Order By: Relevance
“…Almost all randomized studies in patients with mild cognitive impairment (MCI) demonstrate some positive effects on one or several domains of cognition [7]. In one of the largest randomized trials of aerobic exercise in MCI subjects, tests of executive function (Symbol Digit Modalities, Verbal Fluency, and Stroop) showed improvement, whereas memory tests did not, suggesting that certain cognitive domains are more amendable to exercise than others [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all randomized studies in patients with mild cognitive impairment (MCI) demonstrate some positive effects on one or several domains of cognition [7]. In one of the largest randomized trials of aerobic exercise in MCI subjects, tests of executive function (Symbol Digit Modalities, Verbal Fluency, and Stroop) showed improvement, whereas memory tests did not, suggesting that certain cognitive domains are more amendable to exercise than others [8].…”
Section: Introductionmentioning
confidence: 99%
“…In one of the largest randomized trials of aerobic exercise in MCI subjects, tests of executive function (Symbol Digit Modalities, Verbal Fluency, and Stroop) showed improvement, whereas memory tests did not, suggesting that certain cognitive domains are more amendable to exercise than others [8]. In studies of dementia and AD, one recent review [7] and an updated meta-analysis [9] underscore the need for caution in interpreting findings due to methodological issues. Further, some studies in patients with AD or MCI have relied on unsupervised, caregiver supervised, or partly unsupervised exercise [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight was subsequently increased if the participant was able to perform two additional repetitions with good form, or decreased if the participant could not perform the required number of repetitions. A systematic review concluded that long intervention duration, high exercise intensity and good adherence all appear to be important in obtaining cognitive benefits in people with dementia or mild cognitive impairment [35].…”
Section: Exercise Interventionsmentioning
confidence: 99%
“…Of note, participants maintained executive and global cognitive benefits for over 18 months (Fiatarone Singh et al 2014). Conversely, other reports have indicated that exercise may not improve cognitive function in healthy older adults and people with MCI (Gates et al 2013;Ohman et al 2014;Young et al 2015). A Cochrane Review found that aerobic exercise did not improve cognitive function in older adults without known cognitive impairment (Young et al 2015).…”
mentioning
confidence: 98%